2000
DOI: 10.1073/pnas.040558797
|View full text |Cite
|
Sign up to set email alerts
|

Viral persistencein vivothrough selection of neutralizing antibody-escape variants

Abstract: Despite initial virus control by CD8 ؉ cytotoxic T lymphocytes (CTLs), noncytopathic or variably cytopathic viruses (e.g., hepatitis B and C viruses, HIV) are able to establish persistent infections. The role of neutralizing antibodies (nAbs) in controlling disease progression is unclear. Therefore, the phenomenon of viral evasion from the nAb response and its implications for virus persistence remain controversial. Here we demonstrate nAb-mediated viral clearance in CTL-deficient mice infected with the protot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
122
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 140 publications
(132 citation statements)
references
References 54 publications
9
122
1
Order By: Relevance
“…Interestingly, a good relationship between serum anti-HBs and Tim-3 expression on CD8 + T was found in our HBV model mice ( Figure 5 increase in titer when CD8 + T cell function is impaired or absent (25)(26)(27)(28). This competitive coexistence may be beneficial to the host by averting a combination of strong cytotoxicity and antibody responses that may favor immunopathology (31,32).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Interestingly, a good relationship between serum anti-HBs and Tim-3 expression on CD8 + T was found in our HBV model mice ( Figure 5 increase in titer when CD8 + T cell function is impaired or absent (25)(26)(27)(28). This competitive coexistence may be beneficial to the host by averting a combination of strong cytotoxicity and antibody responses that may favor immunopathology (31,32).…”
Section: Discussionmentioning
confidence: 60%
“…It was found that production of serum anti-HBs decreased in Tim-3 shRNA-1-treated HBV model mice compared to that in unshRNAtreated HBV model mice (p < 0.05) ( Figure 5C). Previous reports have shown that neutralizing antibodies increased in titer when the function of CD8 + T cells is impaired or absent in low-cytopathic virus infection (25)(26)(27)(28), indicating the competitive relationship between CD8 + T cell-function and serum anti-HBs. Therefore, our results suggest that Tim-3 might indirectly influence neutralizing antibody production in HBV infection by regulating CD8 + T cell function.…”
Section: Tim-3 Knockdown Up-regulates Ifn- Production From Cd8 + T Cmentioning
confidence: 90%
“…This allows RNA viruses to overcome many challenges imposed by immune systems (Aebischer et al, 1991;Ciurea et al, 2000) or human-engineered antivirals (Melnick et al, 1961). Yet, a cost accompanies this high rate of mutation: the higher the mutation rate, the more likely a progeny virus is to carry a deleterious mutation (Crotty et al, 2001;Eigen and Schuster, 1977).…”
Section: How?mentioning
confidence: 99%
“…Once escape has occurred, it is difficult for cellular responses to regain control due to the phenomena of T cell exhaustion (clonal deletion in the face of continuing viral loads) [66,77] and original sin (inability to generate new responses against emerging variants) [78]. Thus, once this situation is established, chronicity becomes inevitable [79].…”
Section: Success Versus Failure Of T Cell Responses: the Potential Romentioning
confidence: 99%